Mentors' Experiences of Supporting Practitioners to Reflect on their Image of the Child - Dennehy, Breda (Marino Institute of Education, 2019)
This study explored mentors’ experiences of supporting practitioners to reflect on their image of the child. The purpose was to evaluate the effectiveness of making this reflection central to mentoring practices for quality improvement. This study was carried out using qualitative methods of data collection. A narrative enquiry exploring the spoken and written word on the experiences of mentors’. The study employed a multiple methods approach using open response questionnaires and semi-structured focus group discussion. The participants were members of the Better Start mentoring team who are early childhood professionals (Level 8/9) and are qualified in mentoring and coaching. Literature asserts that early years practitioners continuous professional development is central to the professionalisation of ECCE services, and is a critical component in the quality of the experiences afforded to children (Sheridan et al, 2009). Our view of children is where curriculum development should begin (NCCA, 2014). The Aistear Síolta Practice Guide (2014) focuses on the rights of the child and practitioner image of the child to support reflection on the principles that underpin curriculum. This informs a practitioner’s role in supporting children to show their confidence and competence (NCCA, 2006). The Better Start Quality Development service is a mentoring service, which supports providers in implementing the quality standards of Síolta, The National Quality Framework for Early Childhood Education (CECDE, 2006), and Aistear: The National Early Years Curriculum Framework (NCCA, 2009). Mentoring is an effective form of professional development in early childhood settings (Howe & Jacob, 2013). Change facilitated through mentoring is likely to be sustained (Chu, 2014; Garvey, (2004) as it considers the principles of adult learning theory (Knowles, 1970).
Master in Education studies (Early Childhood Education)
Keywords: Research Subject Categories; Mentor; Quality improvement; Image of the child; Reflection; Early Childhood Education and Care (ECEC); Coaching; Curricular framework; Aistear; Síolta